Mechanistic Rationale and Clinical Efficacy of Hyperbaric Oxygen Therapy in Chronic Neuropathic Pain: An Evidence-Based Narrative Review. (22nd April 2021) - Schiavo, Simone; DeBacker, Julian; Djaiani, Carine; Bhatia, Anuj; Englesakis, Marina; Katznelson, Rita
Abstract : Background . Chronic neuropathic pain is a condition affecting an increasing proportion of the general population and its management requires a comprehensive, multidisciplinary program. A growing body of evidence supports the use of hyperbaric oxygen therapy (HBOT) in several chronic neuropathic pain conditions; however, its role and efficacy remain unclear. Purpose . To summarize current evidence for the mechanistic rationale of HBOT in chronic neuropathic pain conditions and to evaluate its clinical efficacy. Methods . This narrative review was conducted after searching the following databases (Medline, Embase, Cochrane, PsycINFO, the Web of Science, Scopus, ClinicalTrials. gov, WHO ICTRP, and ProQuest Digital Dissertation) from January 1946 to March 2020. Articles published in English that involved either animal or human studies with acute or chronic neuropathic pain evaluating any HBOT-related intervention were included. Results . A total of 2971 citations were identified. A total of 29 studies were included in this review. The mechanisms of action for HBOT use in neuropathic conditions included the primary effects of hyperoxia and edema resolution, as well as the secondary effects pertinent to the production of oxygen and nitrogen reactive species (serving as pain signaling molecules), nitric oxide-dependent release of opioid peptides, and reduction of inflammatory mediators. A robust evidence for HBOT use in the clinical setting was associated with chronic regional pain syndrome and chronic primary bladder pain syndrome. Some evidence supported its use for chronic secondary (peripheral) neuropathic pain including radiation-induced plexus neuropathies, postherpetic neuralgia, and trigeminal neuralgia. Conclusions . HBOT has been shown to have antinociceptive and analgesic effects in animal models of inflammatory, neuropathic, and chronic pain. Human studies demonstrated beneficial effects of HBOT in improving clinical outcomes such as pain scores, pain-related symptoms, and quality of life. A systematic methodology of HBOT application is necessary to confirm its safety and efficacy.